Effect of Body Mass Index on Early Morbidity and Mortality After Isolated Coronary Artery Bypass Graft Surgery - ARSAN, SİNAN (W B SAUNDERS CO-ELSEVIER INC, 2012)
Objectives: Obesity is a risk factor for morbidity after isolated coronary artery bypass grafting. This study aimed to analyze the sole effect of body mass index (BMI) on early morbidity and mortality in patients after isolated coronary artery bypass grafting. Design: This study was retrospective and used an electronic database of anesthesia information management. Setting: A single community hospital. Participants: The data of 803 consecutive patients after isolated on-pump coronary artery bypass grafting were analyzed retrospectively; off-pump cases were excluded. Intervention: According to measured BMI, patients were divided into 5 groups: underweight (BMI <20 kg/m(2)), normal weight (BMI 20.0-24.9 kg/m(2)), overweight (BMI 25.0-29.9 kg/m(2)), obese (BMI 30.0-34.9 kg/m(2)), and morbidly obese (BM >34.9 kg/m(2)). Early postoperative morbidity and mortality were evaluated using logistic regression analysis. Measurements and Main Results: Early cumulative postoperative mortality was 3.9% (32 of 803 patients). Mortality was recorded in 3 underweight (n = 15,20%, odds ratio [OR] 6.54, p = 0.001), 9 normal-weight (n = 159, 5.7%, OR 1.62, p = 0.228), 12 overweight (n = 371,3.2%, OR 0.68, p= 0.314), 6 obese (n = 199, 3.0%, OR 0.69, p = 0.421), and 2 morbidly obese (n = 59, 3.4%, OR 0.83, p = 0.808) patients. Prolonged intensive care unit stay (p < 0.001), prolonged hospital stay (p < 0.001), and mortality (p = 0.01) were significantly more common in patients in the underweight group than in the other groups. Univariate and multivariate logistic regression analyses showed that underweight, hypertension, and chronic renal failure were independent risk factors for mortality. Conclusions: Underweight patients with a BMI <20 kg/m(2) are at increased risk of postoperative complications and mortality compared with normal-weight or overweight subjects. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: body mass index; coronary artery bypass; mortality; morbidity; overweight; underweight; CARDIOVASCULAR-DISEASE; RISK-FACTOR; TERM MORTALITY; HEART-DISEASE; OBESITY; OUTCOMES; IMPACT; ASSOCIATION